Analysis of electric characteristics of high-elevation stretches of the tucuruí-macapá-manaus connection - Kurokawa, Sérgio [UNESP]; Costa, Eduardo C. M.; Pinto, André J. G.; Filho, José Pissolato (Springer Nature, 2013)
This article contains a detailed study of the parameters and electric characteristics of a transmission system proposed to electrically connect the cities ofTucuruí,Macapá and Manaus. Several sections of this transmission line will be supported by steel towers 280 m high to suspend the line above the Amazon tropical forest. The height of the line and the presence of two dielectrics in the system-the air and the forest-produce unique line parameters compared to the longitudinal parameters of a conventional line, which is approximately 40 m high. A preliminary analysis of the parameters of a line section of the Tucuruí-Macapá-Manaus connection is conducted in this article. The behaviors of potential surges in the line resulting from switching operations and atmospheric discharges are also investigated. © Brazilian Society for Automatics-SBA 2013.
Keywords: Electromagnetic transients; Transmission line; Tucuruí-Macapá-Manaus connection